Distribution type monitoring system based on CAN bus for dual-fuel ship - SHI GUOWEI; JIANG ZHAOWEI; ZHANG LIANG; PANG CHUNFENG; LI JIEHUI; JIANG JIAQI; CUI YUFENG; ZHONG GUANGYAO; YU HONGWEI (2015)
The utility model relates to a distribution type monitoring system based on a CAN bus for a dual-fuel ship, and the system simultaneously monitors two engines. A human machine interface (HMI) of the Kinco company is used as an upper computer, and after automatically generating codes through Matlab/Simulink based on a model design (MBD), the program of a lower computer is downloaded in a single-chip microcomputer; the upper computer HMI and the lower computer ECU complete data communication through the hardware circuit of the CAN bus, a CAN controller integrated in the single-chip microcomputer is connected with a CAN transceiver so as to realize network protocol standard. The distribution type monitoring system has the following functions: 1, displaying, the actual running parameters and the performance indexes of engines can be displayed in real time; 2, monitoring, the data range can be automatically monitored on line, twinkle is shown when the data exceeds upper and lower limits, and alarm is provided for fire; 3, controlling, contact controls, such as mode switching, fan switch and emergency shut, are manually operated; 4, recording, the running parameters, the state records and the historical data are stored.